Cardiac magnetic resonance including parametric mapping in acute Takotsubo syndrome: Preliminary findings. Issue 113 (April 2019) - Dabir, Darius; Luetkens, Julian; Kuetting, Daniel L.R.; Feisst, Andreas; Isaak, Alexander; Schild, Hans H.; Thomas, Daniel
Highlights: T1 and T2 mapping discriminate between healthy and diseased myocardium in TTS. Mapping may be superior to STIR-imaging for detection of disease involvement in TTS. Mapping has the potential to serve as a reliable marker of disease progress in TTS. Abstract: Introduction: T1 and T2 mapping have been shown to be reliable markers of interstitial myocardial fibrosis, edema, and inflammation. The aim of this study was to evaluate myocardial involvement in acute phase Takotsubo syndrome using native and post-contrast T1 mapping, ECV fraction, and T2 mapping. Material and methods: We investigated 14 patients with acute Takotsubo syndrome and 14 healthy controls. CMR included cine imaging, black-blood STIR imaging, early and late gadolinium enhancement imaging, native and post-contrast T1 mapping, and T2 mapping. Wall motion, T2 ratio, early gadolinium enhancement ratio, extracellular volume fraction, T1 and T2 relaxation times were analyzed. Results: Patients had significantly impaired left ventricular function (46 ± 10%) and acute wall motion abnormalities compared with controls (62 ± 2%). Native T1 and T2 values, T2 ratio, and ECV fraction were significantly higher in patients compared with controls. In patients, native T1 and T2 values as well as T2 ratio were significantly higher in segments with abnormal wall motion compared with normokinetic segments. Native T1 values, T2 relaxation times, T2 ratio, and ECV fraction were significantly higher, post-contrast T1 relaxation times significantly lower in segments with abnormal wall motion compared with segments of controls; except for T2 ratio and post-contrast T1 relaxation times this also held true for patients' segments with normal wall motion. Conclusions: Native T1 and T2 mapping, as well as ECV fraction, discriminate between visually affected vs. unaffected segments in patients with acute Takotsubo syndrome and reveal significant T1 and T2 tissue changes even in visually unaffected segments. Thus, mapping may allow for better detection in convalescent stages of disease and additionally may have the potential to serve as a marker of disease progress. These preliminary findings warrant further investigation in a larger patient cohort.